Utility of enhanced CT for patients with suspected uncomplicated renal colic and no acute findings on non-enhanced CT. Issue 10 (October 2019) - Robert, C.; Gandon, Y.; Peyronnet, B.; Gauthier, S.; Aubé, C.; Paisant, A.
Abstract : AIM: To evaluate the utility of contrast-enhanced computed tomography (CECT) for patients with suspected uncomplicated renal colic (URC) and no abnormalities on non-enhanced computed tomography (NECT). MATERIALS AND METHODS: The hospital institutional review board and ethics committee approved this retrospective study with a waiver of informed consent. Between January 2016 and April 2017, all consecutive adult patients who consulted at the adult Emergency Department (ED) with suspected URC and who had undergone both NECT and CECT were included retrospectively. The primary endpoint was prevalence of CECT-only diagnosis without acute findings on NECT. The risk factors for an acute finding were identified by logistic regression analysis. RESULTS: Among 126 patients with suspected URC, 12 were excluded. Among the 76 patients with no acute findings on NECT, CECT led to find acute lesions in 14/76 (18%) cases, but only 2/76 (3%) resulted in a change of management. Predictive factors of abnormal finding on CECT were: low renal clearance and high leukocyte count with OR 0.96 (95% confidence interval [CI]: 0.93–0.99), p= 0.0189 and OR 5.79 (95% CI: 1.55–21.64), p= 0.0091, respectively. CONCLUSIONS: In most cases, NECT is sufficient for screening patients with suspected URC. If leucocytosis and low renal function are present, stronger consideration may be given to CECT. Highlights: CT injection is not mandatory in cases of uncomplicated renal colic (URC). A normal non-injected CT is often sufficient for patients with URC. If hyperleukocytosis and low renal function are present, injection must be discussed.